WHY WOMEN SHOULD COVER THEIR HEADS AND VEIL THEIR FACES: CLEMENT OF ALEXANDRIA’S UNDERSTANDING OF THE BODY AND HIS RHETORICAL STRATEGIES IN THE PAEDAGOGUS - Desjardins, Michel R. (Scriptura, 2005)
In the context of growing misogyny and introversion in early Christianity, Clement of Alexandria stands out as an advocate of gender equality and respect for the broader Graeco-Roman world. He also does not demonize the body, or sexuality. Why, then, in his Paedagogus, does he encourage women to "wear a veil over their face and a covering on their head?" Helping us to answer this question is Clement’s view of the interconnections between body and soul. Also important is the way he crafts his message so as to make it appeal to his target audience. In the context of modern debates about veiling, Clement’s stance helps us to appreciate that, while religious arguments to support the veiling of women might differ, the core message has remained constant over time and across cultures.